Lexicographic Probabilities and Choice Under Uncertainty - Blume, Lawrence; Brandenburger, Adam; Dekel, Eddie (Econometrica, 1991)
Conventional Bayesian theory of choice under uncertainty, subjective expected utility theory, fails to satisfy the properties of admissibility and existence of well-defined conditional probabilities; weakly dominated acts may be chosen, and the usual definition of conditional probabilities applies only to nonnull events. This paper develops a non-Archimedean variant of subjective expected utility where decisionmakers have lexicographic beliefs. This generalization can be made to satisfy admissibility and yield well-defined conditional probabilities and at the same time allow for "null" events. Copyright 1991 by The Econometric Society.